(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Due to their gluten components which regulate their dough properties, eight varieties of durum wheat-PDW 233, MACS-9, HI-8498, A-9-30-1, Raj 911, Raj 1555 with good quality characteristics and Bijaga yellow, NIDW-15 with poor quality characteristics have been identified. The content of protein in these varieties ranged from 11.1(Yo to 13.8 percent and the content of -carotene from 4.1 to 5.85 ppm with maximum in PDW-233 and minimum in A-9-30-1. Only in the good quality durum varieties was a 45 kD polypeptide present. However, PCR amplification of the genomic DNA from the selected varieties using unique primers of the LMW glutenin gene showed no polymorphism between the go